LANGUAGE BARRIERS IN VISITING LECTURER PROGRAM FOR NON ENGLISH SPEAKING STUDENTS - Putri, Wulandari (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2022)
The increased use of video conference platforms provides opportunities to invite foreign lecturers to give lectures virtually. Despite of beneficial impacts, inviting foreign lecturers might bring challenges to students using English as a foreign language. Therefore, this study was aimed at examining challenges faced by non-English speaking students in attending visiting lecturer classes delivered in English and the potential strategy. The study was an exploratory study conducted in a university in Indonesia. The study involved 118 students from a Study Program taken from two courses. Data were collected through observation and questionnaire. Findings show that language became one of the most challenging barriers in understanding the materials, mostly due to speaking speed of the lecturers and the lack of vocabulary. The lecture summary provided by in-class lecturers could be an alternative to improve learning process. Findings also indicate that the visiting lecturer program could improve students’ language proficiency, especially their vocabulary and listening comprehension. It concludes that visiting lecturer program has a potential to improve students’ language proficiency. However, it is important to provide strategies to help students comprehend the material, such as allocating time for providing a brief summary of the lectures in the student first or second language.